Review of the Criminal Law on the Distribution of Pharmaceutical Sedatives According to Law. No. 17 of 2023 Concerning Selective Health - Faisal, Muhammad; Arief, Amelia (eScience Humanity Journal, 2024)
This study aims to analyze the crime of illegal pharmaceutical preparation circulation according to Law No. 17 of 2023 concerning Health. The circulation of unlicensed pharmaceutical preparations is a serious threat to public health and has the potential to cause significant health impacts. In this study, a normative approach is used to review relevant laws and regulations, especially the provisions in Law No. 17 of 2023 which regulates criminal sanctions for these violations. The study also discusses the role of law enforcement in eradicating the circulation of illegal pharmaceutical preparations and the challenges faced in law enforcement. The results of the study show that although regulations have been tightened, implementation in the field still encounters various obstacles, such as weak coordination between institutions and limited resources. This study recommends increased supervision, more effective law enforcement, and education to the public about the dangers of using illegal pharmaceutical preparations.